2020
DOI: 10.3390/jcm9092998
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15 in Severe Aortic Valve Stenosis: Relationship with Left Ventricular Remodeling and Frailty

Abstract: Background: Frailty is an important outcome predictor in patients with aortic stenosis who are candidates for transcatheter or surgical aortic valve replacement (AVR). Growth/differentiation factor 15 (GDF15) is a cytokine playing a role in the pathophysiology of ventricular remodeling. We assessed its potential role as an independent soluble biomarker of frailty in these patients. Methods: We studied 62 patients (age, mean 79 years, 95% confidence interval (CI) 77–81; 54.8% female) with severe aortic valve st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Only for BNP (r: 0.367; p < 0.001) and IGF-BP2 (r: 0.324; p = 0.003) a moderate correlation and for GDF-15 (r: 0.204; p = 0.014) a weak correlation was found, whereas for other biomarkers a correlation was almost non-existent. Regarding the correlation of GDF-15 and sPAP, the working group around Fabiani et al [38] also showed only slightly higher values with an r: 0.36; p = 0.001. However, in contrast to our study, the same working group could detect a positive correlation between sST2 and sPAP (r: 0.36; p = 0.04) in another publication [39].…”
Section: Discussionmentioning
confidence: 94%
“…Only for BNP (r: 0.367; p < 0.001) and IGF-BP2 (r: 0.324; p = 0.003) a moderate correlation and for GDF-15 (r: 0.204; p = 0.014) a weak correlation was found, whereas for other biomarkers a correlation was almost non-existent. Regarding the correlation of GDF-15 and sPAP, the working group around Fabiani et al [38] also showed only slightly higher values with an r: 0.36; p = 0.001. However, in contrast to our study, the same working group could detect a positive correlation between sST2 and sPAP (r: 0.36; p = 0.04) in another publication [39].…”
Section: Discussionmentioning
confidence: 94%
“…ROC analysis of the study growth factors showed that GDF-15 might serve as a specific and sensitive biomarker for AS stenosis (fair level), and is especially seen in patients with severe AS, but Ang-2 is not significant. The clinical diagnostic significance of circulating GDF-15 in AS patients could be predicted from studies on its role in several cardiovascular diseases and mortality after transcatheter aortic valve replacement [ 1 , 2 , 3 , 4 , 17 ]. Stress conditions affect GDF-15 levels, and this, in turn, affects the regulation of myocyte hypertrophy and is therefore associated with the severity of hypertrophic cardiomyopathy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirm the clinical and diagnostic role of circulating GDF-15 in AS patients [29,30]. The angiogenic markers VEGF-A and FGF-2 are involved in matrix remodeling, and proliferation plays a significant pathophysiological role in the development of AS [31].…”
Section: Discussionmentioning
confidence: 70%